Characterization of alteration zones and intrusive phases for the prospectus "stock of Piedra Sentada" (Saint Lucia) Cauca, Colombia (2009)
The Santa Lucia porphyritic stock is located in Cauca department, in the western flank of the central cordillera, specifically in the Santa Lucia rural settlement of La Sierra municipality. It corresponds to a hypoabyssal body from the Miocene age which intrudes basalts form Barroso - Amaime complex; it is probably inclined in predominant northeast direction. This characterization is based on the log of 5 vertical drillings made and located by the Japan International Cooperation Agency (JICA), in agreement to the reported geophysical anomalies for the area of study. The stock presents mineralogical and hydrothermal characteristics proper of porphyritic gold-copper deposits, and it is genetically related to the emplacement of 4 intrusive pulses of variable composition between dacite-andesite. They are contained in 2 intrusive phases: an early phase characterized by presenting dominant potassic- biotitic alteration and veinlet typical of high temperature (type M, A, EB, B) which presents the major economic interest in the system; and a postmineral phase with dominant propylitic alteration and typical veinlet (type B, D, CI+Ep) located in the interior part of the deposit. The porphyritic stock presents overprint of veinform systems in the south of the deposit; they correspond preliminarily to low-sulfidation epithermal features. Given the present characteristics in the deposit, its presence is  associated to the metallogenic miocene belt existing in the southwestern part of Colombia.